MUTATION IN FKBP10 GENE CAUSE BRUCK SYNDROME 1 (BRKS1) IN A PAKISTANI FAMILY OF PASHTUN ORIGIN - Tauseef, Usman; Ibrahim, Mohsina; Noor, Noshaba; Hanif, Misbah (Journal of Ayub Medical College Abbottabad, 2023)
Background: Bruck syndrome or BRKS1 is an extremely rare condition characterized by the onset of fractures in infancy, joint contractures, short stature, severe limb deformity, and progressive scoliosis. Less than fifty cases of BRKS1 have been reported so far. Here, we report Bruck syndrome 1 in two siblings who belong to a consanguineous Pashtun family living in Karachi. Our first case is a seven years old boy who presented with recurrent fractures, lower limb deformity, and unable to walk. He had markedly reduced bone mineral density (BMD) and a normal bone profile. The other sibling presented at one week of age with arthrogryposis multiplex congenita, post-axial polydactyly of both feet, and spontaneous fracture of the right proximal femur. Genetic testing of our cases was performed in which genomic DNA was enriched for targeted regions using the hybridization-based protocol, and DNA sequencing was done using Illumina technology; both cases were found homozygous for pathogenic variant c.344G>A (p.Arg115Gln) in FKBP10 gene leading to the diagnosis of BRKS1. FKBP10 gene mutation has been reported earlier in association with BRKS1, but in our case report, we have reported the first case of BRKS1, particularly in the Pakistani population of Pashtun ethnicity. We have reported post-axial polydactyly of both feet and spina bifida for the first time in association with FKBP10 mutation. In addition, the skeletal survey of patients with BRKS 1 is elaborated in detail in this report.